ANALISIS INDEPENDENSI AUDITOR INTERNAL DAN AUDITOR EKSTERNAL DI KOTA PADANG (Studi Empiris pada Perusahaan Swasta dan KAP Wilayah Kota Padang) - Silmi Silmi (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2020)
This research aims to find and examine whether external auditors are more independent than internal auditors and the effect of age on auditor independence (Empirical study on private companies and public accounting firms Padang). This research is quantitative research. The population is 7 public accounting firms and 7 private companies in Padang. The sample of this research includes 37 internal auditors and 38 external auditors. The data source is primer data. Data was collected by distributing questionnaire to the private companies and public accounting firms Padang. The method of data analysis is independent sample t-test to examine hypothesis 1 and simple regression to examine hypothesis 2, with independence as dependent variable and age as independent variable. The result of this research show that external auditors are not more independent than internal auditors, where thitung< ttabel -0,852 < 2,02 and (sig 0,397 > 0,05), so hypothesis 1 is not accepted. And age effect on auditors independence where, sig (0,002) < (0,05) and thitung > ttabel, (3,241 > 1,992), so hypothesis 2 is accepted.